2014
DOI: 10.1021/cg5010787
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering of Tolane Bridged Nitronyl Nitroxide Biradicals: Candidates for Quantum Magnets

Abstract: The tolane bridged nitronyl nitroxide biradicals with hydrogen bond donor and acceptor functional groups were synthesized. The magnetic measurements and the DFT calculations were performed to ascertain the influence of the functional groups on inter-and intramolecular magnetic exchange interactions. While upon functionalizing the tolane bridge the intramolecular exchange interactions remained nearly unchanged, the fine-tuning of intermolecular exchange interactions could be achieved by employing the crystal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…The intra‐molecular exchange interactions varied thereby from J intra / k B = −4.6 to −6.4 K being weakest for the strong nitro acceptor in 10 and strongest for 9 with the donor methoxy and Br acceptor. Already a significant difference in the magnetization as a function of magnetic field up to 5 T at 2 K was elucidated as shown in Figure . The increase of magnetization in very low‐field region below 0.1 T for sample 7 could be due to some more impurities but also stem from some ferromagnetic intermolecular interactions J ′ which would need more detailed analysis.…”
Section: Resultsmentioning
confidence: 97%
“…The intra‐molecular exchange interactions varied thereby from J intra / k B = −4.6 to −6.4 K being weakest for the strong nitro acceptor in 10 and strongest for 9 with the donor methoxy and Br acceptor. Already a significant difference in the magnetization as a function of magnetic field up to 5 T at 2 K was elucidated as shown in Figure . The increase of magnetization in very low‐field region below 0.1 T for sample 7 could be due to some more impurities but also stem from some ferromagnetic intermolecular interactions J ′ which would need more detailed analysis.…”
Section: Resultsmentioning
confidence: 97%
“…Serendipitously during the course of our study on organic biradical systems for the Bose-Einstein condensation we found the molecule BPNO (N,N'-([1,1'-biphenyl]-4,4'-diyl)bis(N-(tertbutylaminoxyl)) which exists in semi-quinoid form ( Figure 3). [27][28][29] At room temperature BPNO showed doublet EPR spectrum. Even after several purifications by column followed by repetitive crystallization no improvement in EPR spectrum was observed.…”
Section: Introductionmentioning
confidence: 98%
“…[21][22] The calculations were executed with the Gaussian 09 program package 23 employing the unrestricted 24 BLYP functional [25][26][27] and the 6-31G(d) basis set. 28 The geometry of biradical 2,7-TMPNO was taken from X-ray diffraction determinations without further optimization.…”
Section: Dft Calculationsmentioning
confidence: 99%